COMMUNITY SERVICE EVALUATION OF TOURISM MARKETING TRAINING AT STATE VOCATIONAL SCHOOL 2 SEKOTONG - Sutarini, Ida Ayu; Maulida, Novita; Amy, Najamuddin (Jurnal Pepadu, 2024)
Community service (PkM) is one of the Tri Dharma programs of higher education institutions that must be carried out by every lecturer. The Communication Studies Program at Unram conducted a community service activity on Saturday, May 4, 2024, at SMK Negeri 2 Sekotong titled "Social Media Management Training to Enhance Tourism Marketing Competence at SMK Negeri 2 Sekotong." The purpose of this evaluation is to explain the partners' perceptions of the implementation process of the PkM activities through the Context, Input, Process, and Product model. (CIPP). The descriptive quantitative method used illustrates the evaluation results of the PkM activity implementation process. There was no treatment, manipulation, or data alteration on the independent variable. The sample for this evaluation consisted of 30 students from SMK Negeri 2 Sekotong who participated in the PkM activities. The data collection method involved distributing questionnaires to the participants. The data analysis results showed that the evaluation of the PkM activities conducted by the lecturers of the Communication Studies Program at Universitas Mataram through Context, Input, Process, and Product (CIPP) achieved an overall average of 87%, which falls into the category of Very Suitable according to the partners' expectations. Therefore, the quality of this activity in terms of the CIPP aspects needs to be maintained or further improved in the next PkM activities.